N‐Acetylcysteine, a glutathione precursor, reverts vascular dysfunction and endothelial epigenetic programming in intrauterine growth restricted guinea pigs - Herrera, Emilio A. (J Physiol, 2016)
KEY POINTS: Intrauterine growth restriction (IUGR) is associated with vascular dysfunction, oxidative stress and signs of endothelial epigenetic programming of the umbilical vessels. There is no evidence that this epigenetic programming is occurring on systemic fetal arteries. In IUGR guinea pigs we studied the functional and epigenetic programming of endothelial nitric oxide synthase (eNOS) (Nos3 gene) in umbilical and systemic fetal arteries, addressing the role of oxidative stress in this process by maternal treatment with N‐acetylcysteine (NAC) during the second half of gestation. The present study suggests that IUGR endothelial cells have common molecular markers of programming in umbilical and systemic arteries. Notably, maternal treatment with NAC restores fetal growth by increasing placental efficiency and reverting the functional and epigenetic programming of eNOS in arterial endothelium in IUGR guinea pigs. ABSTRACT: In humans, intrauterine growth restriction (IUGR) is associated with vascular dysfunction, oxidative stress and signs of endothelial programming in umbilical vessels. We aimed to determine the effects of maternal antioxidant treatment with N‐acetylcysteine (NAC) on fetal endothelial function and endothelial nitric oxide synthase (eNOS) programming in IUGR guinea pigs. IUGR was induced by implanting ameroid constrictors on uterine arteries of pregnant guinea pigs at mid gestation, half of the sows receiving NAC in the drinking water (from day 34 until term). Fetal biometry and placental vascular resistance were followed by ultrasound throughout gestation. At term, umbilical arteries and fetal aortae were isolated to assess endothelial function by wire‐myography. Primary cultures of endothelial cells (ECs) from fetal aorta, femoral and umbilical arteries were used to determine eNOS mRNA levels by quantitative PCR and analyse DNA methylation in the Nos3 promoter by pyrosequencing. Doppler ultrasound measurements showed that NAC reduced placental vascular resistance in IUGR (P < 0.05) and recovered fetal weight (P < 0.05), increasing fetal‐to‐placental ratio at term (∼40%) (P < 0.001). In IUGR, NAC treatment restored eNOS‐dependent relaxation in aorta and umbilical arteries (P < 0.05), normalizing eNOS mRNA levels in EC fetal and umbilical arteries (P < 0.05). IUGR‐derived ECs had a decreased DNA methylation (∼30%) at CpG −170 (from the transcription start site) and this epigenetic signature was absent in NAC‐treated fetuses (P < 0.001). These data show that IUGR‐ECs have common molecular markers of eNOS programming in umbilical and systemic arteries and this effect is prevented by maternal treatment with antioxidants.